Internalisation of Religious Culture Through Non-Academic Learning Process Based on Islamic Religion - Tiara, Hellen; Zainuri, Ahmad; Astrid, Annisa (LETIGES, 2026)
This research aims to examine the internalisation of religious culture through non-academic learning processes at Senior High School 15 Palembang. It focuses on how these schools implement Islamic-based religious practices and values to nurture students’ spiritual growth. This qualitative study employs field research with data collected through observation, interviews, and documentation. A descriptive qualitative analysis was conducted through data collection, reduction, presentation, and verification. The findings reveal that the internalisation of religious culture in these schools integrates Islamic values into students' behaviours and attitudes. Religious practices are primarily promoted through non-academic activities outside the formal Islamic Education, Al-Islam, and Fiqh classes. Students demonstrate these values in both school and community settings, participating in structured religious activities such as congregational prayers, Quran recitation (tadarus), Dhuha prayers, and embodying respectful behaviours such as politeness and friendliness. These practices are intended to foster students' development into morally grounded individuals who contribute positively to societal ethics. The study also highlights the need for improved facilities, such as dedicated prayer areas, to support the internalisation of religious culture further. The study focuses on three schools in Palembang, which may limit the generalizability of the findings to other contexts. Future research could expand the scope to include a variety of educational institutions and regions. This research provides insights into how religious culture can be systematically internalised through non-academic activities within Islamic educational settings. It underscores the role of leadership, habitual practices, and supportive environments in promoting the ethical and spiritual development of students, bridging modern educational goals with Islamic moral principles.